Características de adensamento com drenagem radial de uma argila mole da Baixada Fluminense - Coutinho, Roberto Quental (1976)
This dissertation, as a contribution to the study of problems in construction of embankments on natural soft clay deposits, presents and discusses laboratory vertical and radial drainage consolidation charactheristics with the influence of communly used sand drain installation methods. A partial bibliography review on vertical sand drains is presented. Results of vertical and radial (internal and external drainage) oedometer consolidation and triaxial consolidation tests with radial internal drainage are presented. The influence of undesirable boundary conditions in oedometer tests with radial internal drainage is shown. Disturbance effect on some consolidation charactheristics has been examined. The coefficient of secondary compression (Cα) and the effect on it due to sand drain installation rnethod has been tentatively evaluated. The influence on undrained shear strength due the installation of vertical sand drains by the closed madrel method has also been tentatively evaluated.